2022
DOI: 10.1371/journal.pgph.0000820
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 infection in Baja California, Mexico: Findings from a community-based survey in February 2021 in the Mexico-United States border

Abstract: Between March 2020 and February 2021, the state of Baja California, Mexico, which borders the United States, registered 46,118 confirmed cases of COVID-19 with a mortality rate of 238.2 deaths per 100,000 residents. Given limited access to testing, the population prevalence of SARS-CoV-2 infection is unknown. The objective of this study is to estimate the seroprevalence and real time polymerase chain reaction (RT-PCR) prevalence of SARS-CoV-2 infection in the three most populous cities of Baja California prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…One of the likely causes of the COVID‐19 virus' quick proliferation in Ethiopia was reported to be the constant flow of immigrants and the inadequate border protection 33 . Likewise similar high prevalence rates in border towns and cities were reported in Ruili City of China‐Myanmar border 34 and in Baja California of Mexico‐USA border 35 …”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…One of the likely causes of the COVID‐19 virus' quick proliferation in Ethiopia was reported to be the constant flow of immigrants and the inadequate border protection 33 . Likewise similar high prevalence rates in border towns and cities were reported in Ruili City of China‐Myanmar border 34 and in Baja California of Mexico‐USA border 35 …”
Section: Discussionmentioning
confidence: 67%
“…33 Likewise similar high prevalence rates in border towns and cities were reported in Ruili City of China-Myanmar border 34 and in Baja California of Mexico-USA border. 35 High seroprevalence rate reported in Jigjiga district might be due to its large population size and relatively urbanization, where there is considerable overcrowding. Higher seroprevalence levels were observed in cities with large populations in Colombia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zazueta et al ( 10 ), during the COVID-19 pandemic, face mask usage was reported to be up to 89%. According to Bults et al ( 4 ), the face mask usage during the H1N1 pandemic was of 71%.…”
Section: Methodsmentioning
confidence: 99%